2020
DOI: 10.1111/andr.12785
|View full text |Cite
|
Sign up to set email alerts
|

Semen endocannabinoids are correlated to sperm quality in a cohort of 200 young Swiss men

Abstract: Background A role for endocannabinoids in the male and female reproductive systems has been highlighted during the recent decades. Some of these compounds bind the cannabinoid CB1 receptor, which is abundantly expressed in the central nervous system but also present in the reproductive system, while others act as ‘entourage compounds’ modulators. Objectives The present study aimed at evaluating the relationship between sperm quality and endocannabinoid profiles in a cohort of 200 young Swiss men and whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Similar results were obtained by the same group in PRL-responsive human prostate DU-145 cancer cells in which the PRL-induced cell growth was potently inhibited by both AEA and 2-AG [200]. Furthermore, Bifulco's group [22,207] found that CB1 receptor stimulation by AEA reduced cell proliferation in both ER-positive and ER-negative breast cancer cells being effective in inhibiting adhesion, migration as well as the epithelial-mesenchymal transition during cancer progression [188]. The intriguing effect of ECS stimulation as a cancer suppressor in estrogen-dependent tumors was furtherly investigated starting from the observation that 17β estradiol was capable to induce CB1 receptor expression in colon cancer cells [218].…”
Section: Interactions Of Ecs and Es In Cancersupporting
confidence: 78%
See 2 more Smart Citations
“…Similar results were obtained by the same group in PRL-responsive human prostate DU-145 cancer cells in which the PRL-induced cell growth was potently inhibited by both AEA and 2-AG [200]. Furthermore, Bifulco's group [22,207] found that CB1 receptor stimulation by AEA reduced cell proliferation in both ER-positive and ER-negative breast cancer cells being effective in inhibiting adhesion, migration as well as the epithelial-mesenchymal transition during cancer progression [188]. The intriguing effect of ECS stimulation as a cancer suppressor in estrogen-dependent tumors was furtherly investigated starting from the observation that 17β estradiol was capable to induce CB1 receptor expression in colon cancer cells [218].…”
Section: Interactions Of Ecs and Es In Cancersupporting
confidence: 78%
“…An inverse relationship between sperm motility and AEA concentrations in seminal fluid and OEA levels in blood serum has been found; conversely, PEA levels in semen were positively linked to sperm concentration, whereas in seminal fluid the levels of OEA and PEA-that exhibit antioxidants properties [189]-were associated with better sperm morphology. The presence of urinary THC-COOH (an inactive metabolite of ∆ 9 -THC), used as an indicator of cannabis consumption, in n = 15 individuals has been linked to lower concentrations of endocannabinoids in semen and low circulating AEA in blood, suggesting a possible ∆ 9 -THC-mediated negative feedback on AEA production and concentration; by contrast, no correlation was observed between the presence of urinary bisphenols and endocannabinoids [188].…”
Section: Es and Ecs Modulation By Estrogens-like Substances Affecting Cns And Gonadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly endocrine disruption was identified as one possible mechanism to explain this relationship [ 7 ]. Cannabis is a well established endocrine disruptor [ 49 59 ]. Whilst there are no extant papers documenting the relationship of cannabinoid exposure to ovarian cancers oocytes have been shown to be highly sensitive to cell death during cell division under the influence of cannabinoids [ 60 ] and the ovary is also known to be highly sensitive to inhibitors of mitochondrial metabolism a role which several cannabinoids including cannabidiol have long been known to play [ 36 , 37 , 61 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Δ 9 -THC-COOH response corroborates our Δ 9 -THC findings, as this metabolite is used as an indicator of cannabis consumption owing to Δ 9 -THC rate of oxidation and stability of Δ 9 -THC-COOH, 48 and its reported association with low AEA at high concentrations. 61 Impact on AEA may be a consequence of Δ 9 -THC-CB 1 R-activated AEA membrane transport 62 for intracellular degradation by FAAH. 63 Alternatively, AEA synthesis has been described as an “on-demand” process linked to its receptor coupling.…”
Section: Discussionmentioning
confidence: 99%